Effect of seat shear forces and pressure on perceived sitting comfort in cycling - Scholler, V.; Groslambert, A.; Grappe, F. (Journal of Science and Cycling, 2023)
Feeling comfortable on the bicycle is essential for professional cyclists to decrease pain and prevent pathologies. The pressure analysis appears to be a relevant tool to monitor how the changes in position and saddle characteristics affect the stress on genital tissues to prevent pathologies. Moreover, in everyday life sitting situations, other biomechanical sitting parameters such as shear forces influence the sitting comfort. Therefore, this study aimed to identify how the seat pressure and shear forces affect the perceived sitting comfort of twelve competitive road cyclists during a 20 min treadmill cycling exercise. Treadmill exercises were performed before and after a fitting optimization session that aimed to improve the perceived sitting comfort. The major result is that the fitting optimization session significantly improved the perceived sitting comfort by 77%. Such improvement was associated with the decrease in shear forces (-21±42%) applied by the cyclist on the saddle in the lateral-medial direction and the increase in peak pressure at sit bone left (+19±25%) and right (+28±63%) following the fitting optimization session. It would be induced by better stability of the cyclist`s pelvic on the saddle, therefore reducing the proportion of the shear forces applied on the saddle.